Ultrasonic sensor structure for enhancing high-temperature service performance and preparation method thereof

By introducing a high-entropy alloy oxide protective layer into the sensor structure and combining it with a specific preparation method, the problem of sensor damage under high temperature conditions was solved, higher resistance and stability were achieved, and the high-temperature service performance of the sensor was enhanced.

CN121099893APending Publication Date: 2025-12-09SPECIAL EQUIP SAFETY SUPERVISION INSPECTION INST OF JIANGSU PROVINCE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511090134.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Traditional piezoelectric sensors are easily damaged in high-temperature environments, resulting in reduced reliability and lifespan. Existing technologies are difficult to operate reliably for a long time in high-temperature environments.

Method used

An ultrasonic sensor structure, consisting of a substrate, a piezoelectric layer, a protective layer, a bonding layer, and an electrode layer, was fabricated using a high-entropy alloy oxide as a protective layer, combined with radio frequency magnetron sputtering and arc ion plating. This improved the sensor's high-temperature stability and reliability.

Benefits of technology

It significantly improves the resistance value of the sensor, prevents the piezoelectric layer from being broken down during high-voltage testing, and enhances the working stability and durability of the sensor in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121099893A_ABST
    Figure CN121099893A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrasonic sensor structure capable of enhancing high-temperature service performance and a preparation method thereof, and belongs to the technical field of piezoelectric sensors, the ultrasonic sensor structure sequentially comprises a substrate, a piezoelectric layer, a protective layer, a bonding layer and an electrode layer from bottom to top, and the ultrasonic sensor structure is characterized in that the protective layer is a high-entropy alloy oxide with the thickness of 1-10 microns, and the high-entropy alloy oxide is selected from at least one of AlCrNbSiTiO, AlCrNiSiTiTaYO, AlCrNbSiTaTiO, AlCrNbSiTaTiVO, AlCrNbSiTaTiVO, AlCrNbSiTaTiVO, AlCrNbSiTaTiZrO and AlCrNbSiTiVO. The high-entropy alloy oxide protection layer is adopted, the resistance of the sensor is remarkably improved, the piezoelectric layer can be prevented from being broken down in the high-voltage testing process, the working stability of the sensor in the high-voltage environment is improved, and the high-entropy alloy oxide protection layer can serve as a high-temperature protection layer to improve the high-temperature stability of the sensor.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of piezoelectric sensors, in particular to an ultrasonic sensor structure with enhanced high-temperature service performance and a preparation method thereof. BACKGROUND

[0002] At present, there are many stress detection technologies, but torque method, calendering method, optical fiber method, gasket method and the like have large errors, and traditional ultrasonic wave measurement technologies such as laser and electromagnetic are limited by the size of bolt materials, the ultrasonic energy is weak, and are only suitable for small size bolts. The standards such as ASME-III-5-HBB of the United States and VDI2230 of Germany for the structural health assessment of fasteners such as bolts still stop at calculation and prediction. The piezoelectric film ultrasonic wave method is based on acoustic-elastic effect, and the sound speed and signal strength are affected by stress and load state, so the bolt pretightening force can be predicted in real time and online through the change of ultrasonic wave form, which is efficient, convenient, high-precision (<5%) and high-reliability, and is the most promising high-precision and high-reliability stress sensing and monitoring technology for bolts. Based on this, Intellifast of Germany, Johnson of the United States and the like have realized high-precision measurement of bolt axial force, and have been successfully applied to bolt fastening and installation stage and pretightening force control of companies such as NASA and SpaceX.

[0003] In order to realize the piezoelectric ultrasonic wave method for stress online monitoring, the first problem to be solved is to develop a piezoelectric film material and a sensor which can operate reliably for a long time in a high-temperature environment. The traditional piezoelectric sensor structure includes a piezoelectric layer, a protective layer, a bonding layer and an electrode layer. The protective layer is usually made of SiO2. Although SiO2 can prevent the piezoelectric layer from being broken down during high-voltage testing, the piezoelectric layer is easily damaged at high temperature, which reduces the reliability and service life of the whole sensor. Therefore, it is necessary to improve the protective layer material of the piezoelectric sensor to improve the high-temperature resistance of the sensor. SUMMARY

[0004] In order to overcome the problem that the piezoelectric layer is easily damaged at high temperature and the reliability and service life of the whole sensor are reduced in the prior art, the present application provides an ultrasonic sensor structure with enhanced high-temperature service performance and a preparation method thereof, which are as follows.

[0005] An ultrasonic sensor structure with enhanced high-temperature service performance comprises, from bottom to top, a substrate, a piezoelectric layer, a protective layer, a bonding layer and an electrode layer. The protective layer is a high-entropy alloy oxide with a thickness of 1-10 microns. The high-entropy alloy oxide is selected from at least one of AlCrNbSiTiO, AlCrNiSiTiTaYO, AlCrNbSiTaTiO, AlCrNbSiTaTiVO, AlCrNbSiTaTiVZrO, AlCrSiTaTiZrO and AlCrNbSiTiVO.

[0006] Further, the piezoelectric layer is an oxide or nitride piezoelectric material, and has a thickness of 5-25 microns.

[0007] Further, the bonding layer is at least one metal material selected from Cr and Ti, and has a thickness of 100-600 nm.

[0008] Further, the electrode layer is a solid metal element or a solid metal alloy, and has a thickness of 2-20 microns, and the electrode layer is divided into an inner electrode region and an outer electrode region.

[0009] The application further provides a preparation method of the ultrasonic sensor structure, and has the characteristics that the piezoelectric layer, the protective layer, the bonding layer and the electrode layer are sequentially prepared on the surface of the substrate; the piezoelectric layer, the protective layer and the electrode layer are prepared by using a radio frequency magnetron sputtering method; and the bonding layer is prepared by using an arc ion plating method.

[0010] Further, the target-substrate distance is 5-15 cm, the vacuum degree is 2x10 -3 ~6x10 -3 Pa, and the plating temperature is 40-200 DEG C during the deposition of the radio frequency magnetron sputtering method; and the arc current is 80-110 A, and the gas pressure is 0.8-1.5 Pa during the deposition of the arc ion plating method.

[0011] Further, the piezoelectric layer is an oxide, and Ar and O2 are inputted during the preparation, the gas pressure is 0.8-2.1 Pa, the Ar / O2 flow ratio is (1-6):1, the radio frequency power is 800-900 W, the bias voltage is 0-30 V, and the plating time is 4-10 h.

[0012] Further, the piezoelectric layer is a nitride, and Ar and N2 are inputted during the preparation, the gas pressure is 0.8-2.1 Pa, the Ar / N2 flow ratio is (1-3):1, the radio frequency power is 800-900 W, and the plating time is 4-10 h.

[0013] The application further provides a temperature detection system, which comprises the ultrasonic sensor structure, and the ultrasonic signal intensity of the sensor structure is maintained to be more than 20% of that before annealing after the sensor structure is annealed at a high temperature environment of 760 DEG C for 100 h.

[0014] Further, the sensor structure has a resistance value of 1.0-2.3 MΩ at a measurement frequency of 100 Hz.

[0015] The protective layer has a thickness of 1-10 microns, and the thickness and the resistance value are positively correlated; when the thickness is more than 10 microns, the protective layer is easy to crack, resulting in the failure of the sensor.

[0016] Compared with the prior art, the application has the following beneficial effects:

[0017] The prepared sensor adopts a high-entropy alloy oxide protective layer, which significantly improves the sensor resistance, can not only prevent the piezoelectric layer from being broken down in the high-voltage test process, improve the working stability of the sensor in the high-voltage environment, but also can be used as a high-temperature protective layer to improve the high-temperature stability of the sensor. BRIEF DESCRIPTION OF DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiment or prior art description. Obviously, the drawings in the following description are only some embodiments of the present application, and for those skilled in the art, other drawings can also be obtained without creative labor on the basis of these drawings.

[0019] Figure 1 is a schematic diagram of the high-temperature-resistant piezoelectric thin film sensor structure of the present application;

[0020] Figure 2 is the cross-sectional morphology, Cr element distribution, AlCrNiSiTiTaY electrode layer surface morphology, and AlCrNiSiTiTaYO high-entropy alloy oxide protective layer surface morphology of the high-temperature-resistant piezoelectric thin film sensor structure of the present application;

[0021] Figure 3 is the ultrasonic signal diagram of the sensor structure prepared in Example 1 and Comparative Example 1 of the present application;

[0022] Figure 4 is the ultrasonic signal diagram of the sensor structure prepared in Example 2 and Comparative Example 1 of the present application;

[0023] Figure 5 is the resistance diagram of the sensor structure prepared in Example 1 and Comparative Example 2 of the present application;

[0024] Figure 6 is the resistance diagram of the sensor structure prepared in Example 2 and Comparative Example 3 of the present application;

[0025] Figure 7 is the resistance diagram of the sensor structure prepared in Example 1, Example 3, Example 4 and Comparative Example 2 of the present application;

[0026] Figure 8 is the ultrasonic signal diagram of the sensor structure prepared in Example 1, Example 3, Example 4 and Comparative Example 5 of the present application;

[0027] Figure 9 is the ultrasonic signal diagram of the sensor prepared in Example 5 and Comparative Example 4 of the present application after high-temperature annealing at 760℃.

[0028] In the figure, 1 is a substrate; 2 is a piezoelectric layer; 3 is a protective layer; 4 is a bonding layer; and 5 is an electrode layer. DETAILED DESCRIPTION

[0029] In order to make the objectives, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the embodiments of the present application. Obviously, the described embodiments are only some but not all of the embodiments of the present application. Therefore, the following detailed description of the embodiments of the present application provided in the drawings is not intended to limit the scope of the claimed present application, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative efforts are within the scope of the present application.

[0030] The present embodiment adopts a high-entropy alloy oxide protective layer, which significantly improves the sensor resistance, not only prevents the piezoelectric layer from being broken down during high-voltage testing, and improves the working stability of the sensor in a high-voltage environment, but also serves as a high-temperature protective layer to improve the high-temperature stability of the sensor. The specific implementation is as follows:

[0031] Referring to Figure 1 As shown in the figure, an ultrasonic sensor structure with enhanced high-temperature service performance includes, from bottom to top, a substrate 1, a piezoelectric layer 2, a protective layer 3, a bonding layer 4, and an electrode layer 5. The protective layer 3 is a high-entropy alloy oxide with a thickness of 1-10 μm. The high-entropy alloy oxide is selected from at least one of AlCrNbSiTiO, AlCrNiSiTiTaYO, AlCrNbSiTaTiO, AlCrNbSiTaTiVO, AlCrNbSiTaTiVZrO, AlCrSiTaTiZrO, and AlCrNbSiTiVO.

[0032] Here, the high-entropy alloy oxide refers to a single-phase oxide ceramic composed of five or more main metal elements, which has a high-entropy effect and excellent high-temperature stability.

[0033] As a preferred embodiment, the piezoelectric layer 2 is an oxide or nitride piezoelectric material with a thickness of 5-25 μm.

[0034] As a preferred embodiment, the bonding layer 4 is at least one metal material selected from Cr and Ti, and has a thickness of 100-600 nm.

[0035] As a preferred embodiment, the electrode layer 5 is a solid metal element or a solid metal alloy, and has a thickness of 2-20 μm. The electrode layer 5 is divided into an inner electrode region and an outer electrode region.

[0036] Here, the substrate 1 can be a stainless steel plate, a silicon wafer, a bolt, etc., the material of the piezoelectric layer 2 can be LiNbO3, AlN, ZnO, and metal-doped LiNbO3, AlN, ZnO, etc., and the material of the electrode layer 5 can be Ag, Cr, Ti, etc., AgCr, a high-entropy alloy, etc.

[0037] Here, the electrode layer is divided into an inner electrode area and an outer electrode area, the inner electrode area is used for ultrasonic signal excitation, and the outer electrode area is used for shielding interference and improving signal-to-noise ratio.

[0038] The embodiment also provides a preparation method of the above ultrasonic sensor structure, characterized by sequentially preparing the piezoelectric layer 2, the protective layer 3, the bonding layer 4, and the electrode layer 5 on the surface of the substrate 1; wherein the piezoelectric layer 2, the protective layer 3, and the electrode layer 5 are prepared by a radio frequency magnetron sputtering method; and the bonding layer 4 is prepared by an arc ion plating method.

[0039] As a preferred embodiment, the target-substrate distance is 5-15 cm, the vacuum degree is 2x10 -3 ~6x10 -3 Pa, and the plating temperature is 40-200℃ during deposition by the radio frequency magnetron sputtering method; and the arc current is 80-110 A and the gas pressure is 0.8-1.5 Pa during deposition by the arc ion plating method.

[0040] As a preferred embodiment, the piezoelectric layer 2 is an oxide, Ar and O2 are input during preparation, the gas pressure is 0.8-2.1 Pa, the Ar / O2 flow ratio is (1-6):1, the radio frequency power is 800-900 W, the bias voltage is 0-30 V, and the plating time is 4-10 h.

[0041] As a preferred embodiment, the piezoelectric layer 2 is a nitride, Ar and N2 are input during preparation, the gas pressure is 0.8-2.1 Pa, the Ar / N2 flow ratio is (1-3):1, the radio frequency power is 800-900 W, and the plating time is 4-10 h.

[0042] The embodiment also provides a temperature detection system comprising the above ultrasonic sensor structure, and the ultrasonic signal intensity of the sensor structure remains more than 20% of that before annealing after the sensor structure is annealed at a high-temperature environment of 760℃ for 100 h.

[0043] As a preferred embodiment, the resistance value of the sensor structure is 1.0-2.3 MΩ at a measurement frequency of 100 Hz.

[0044] The high-entropy alloy oxide protective layer has a thickness of 1-10 μm, and the thickness and the resistance value are positively correlated; when the thickness is greater than 10 μm, the protective layer is prone to cracking, leading to failure of the sensor.

[0045] Embodiment 1

[0046] A preparation method of an ultrasonic sensor structure with enhanced high-temperature service performance, the specific steps are as follows:

[0047] First step, prepare a clean stainless steel substrate 1, install it in a radio frequency magnetron sputtering film coating machine, the target-substrate distance is 5 cm, the vacuum degree is 5*10 -3 Pa, the film coating temperature is 200℃;

[0048] Second step, input Ar and O2, the gas pressure is 1.8 Pa, the Ar / O2 flow ratio is 2:1, the radio frequency power is 900 W, the bias voltage is 0 V, the film coating time is 8 h, and a LiNbO3 piezoelectric layer 2 with a thickness of about 16.7 μm is deposited.

[0049] Third step, place the substrate 1 with the deposited piezoelectric layer 2 in the film coating machine, the target-substrate distance is 7 cm, the vacuum degree is 5*10 -3 Pa, the film coating temperature is 50℃;

[0050] Fourth step, input Ar and O2, the gas pressure is 0.9 Pa, the Ar / O2 flow ratio is 1:1, the radio frequency power is 700 W, the film coating time is 5.5 h, and an AlCrNiSiTiTaYO high-entropy alloy oxide protective layer 3 with a thickness of about 4.0 μm is deposited, and the sample is taken out when the temperature in the chamber is lower than 50℃.

[0051] Fifth step, paste an insulating ring on the substrate 1 with the deposited piezoelectric layer 2 and high-entropy alloy oxide protective layer 3, the purpose of the insulating ring is to form an inner and outer electrode area, which is convenient for ultrasonic signal testing, the insulating ring is made of polyester amide material, with a thickness of 0.15 mm, an inner circle diameter of 3 mm, and an outer circle diameter of 5 mm.

[0052] Sixth step, place the sample prepared in the fifth step in the film coating machine, the target-substrate distance is 12 cm, the vacuum degree is 5*10 - 3 Pa, the film coating temperature is 50℃;

[0053] Seventh step, input Ar, the gas pressure is 0.9 Pa, the arc current is 100 A, the film coating time is 1.5 min, and a Cr bonding layer 4 with a thickness of about 500 nm is deposited.

[0054] Eighth step, rotate the sample prepared in the seventh step to face the electrode target material, the target-substrate distance is 7 cm, the vacuum degree is 5*10 -3 Pa, the film coating temperature is 50℃;

[0055] Ninth step, input Ar, the gas pressure is 0.9 Pa, the radio frequency power is 700 W, the film coating time is 1 h, and an AlCrNiSiTiTaY electrode layer 5 with a thickness of about 6.7 μm is deposited, and the sample is taken out when the temperature in the chamber is lower than 50℃.

[0056] Example 2

[0057] A method for preparing an ultrasonic sensor structure with enhanced high-temperature service performance, comprising the following specific steps:

[0058] In the first step, a clean stainless steel substrate 1 is prepared and placed in a radio frequency magnetron sputtering coating machine, the target-substrate distance is 5 cm, the vacuum degree is 5*10 -3 Pa, and the coating temperature is 200℃;

[0059] In the second step, Ar and O2 are input, the gas pressure is 1.8 Pa, the Ar / O2 flow ratio is 2:1, the radio frequency power is 900 W, the bias voltage is 0 V, the coating time is 8 h, and a LiNbO3 piezoelectric layer 2 with a thickness of about 16.7 μm is deposited.

[0060] In the third step, the substrate 1 with the deposited piezoelectric layer 2 is placed in the coating machine, the target-substrate distance is 7 cm, the vacuum degree is 5*10 -3 Pa, and the coating temperature is 50℃;

[0061] In the fourth step, Ar and O2 are input, the gas pressure is 0.9 Pa, the Ar / O2 flow ratio is 1:1, the radio frequency power is 700 W, the coating time is 5.5 h, and an AlCrNiSiTiTaYO high-entropy alloy oxide protective layer 3 with a thickness of about 4.0 μm is deposited, and the sample is taken out when the temperature in the chamber is lower than 50℃.

[0062] In the fifth step, an insulating ring is pasted on the substrate 1 with the deposited piezoelectric layer 2 and high-entropy alloy oxide protective layer 3, the purpose of the insulating ring is to form an inner and outer electrode area, which is convenient for ultrasonic signal testing, the insulating ring is made of polyester amide material, with a thickness of 0.15 mm, an inner diameter of 3 mm, and an outer diameter of 5 mm.

[0063] In the sixth step, the sample prepared in the fifth step is placed in the coating machine, the target-substrate distance is 12 cm, the vacuum degree is 5*10 - 3 Pa, and the coating temperature is 50℃;

[0064] In the seventh step, Ar is input, the gas pressure is 0.9 Pa, the arc current is 100 A, the coating time is 1.5 min, and a Cr bonding layer 4 with a thickness of about 500 nm is deposited.

[0065] In the eighth step, the sample prepared in the seventh step is rotated to face the electrode target material, the target-substrate distance is 7 cm, the vacuum degree is 5*10 -3 Pa, and the coating temperature is 50℃;

[0066] In the ninth step, Ar is input, the gas pressure is 0.9 Pa, the Ag electrode layer 5 is prepared by radio frequency magnetron sputtering method, the radio frequency power is 700 W, the coating time is 11 min, an Ag electrode layer 5 with a thickness of about 6.7 μm is deposited, and the sample is taken out when the temperature in the chamber is lower than 50℃.

[0067] Example 3

[0068] A method for preparing an ultrasonic sensor structure with enhanced high-temperature service performance is basically the same as that in Example 1, except that the plating time in the fourth step is 8 h, and an AlCrNiSiTiTaYO high-entropy alloy oxide protective layer 3 with a thickness of about 5.8 μm is deposited.

[0069] Example 4

[0070] A method for preparing an ultrasonic sensor structure with enhanced high-temperature service performance is basically the same as that in Example 1, except that the plating time in the fourth step is 11 h, and an AlCrNiSiTiTaYO high-entropy alloy oxide protective layer 3 with a thickness of about 8 μm is deposited.

[0071] Example 5

[0072] A method for preparing an ultrasonic sensor structure with enhanced high-temperature service performance is basically the same as that in Example 1, except that the plating time in the fourth step is 11 h, and an AlCrNiSiTiTaYO high-entropy alloy oxide protective layer 3 with a thickness of about 8 μm is deposited.

[0073] First, a clean stainless steel substrate 1 is prepared and placed in a radio frequency magnetron sputtering plating machine, the target-to-substrate distance is 6 cm, the vacuum degree is 4 × 10 -3 Pa, and the plating temperature is 150℃;

[0074] Second, Ar and O2 are input, the gas pressure is 1.5 Pa, the Ar / N2 flow ratio is 2:1, the radio frequency power is 900 W, the bias voltage is 0 V, the plating time is 7 h, a LiNbO3 piezoelectric layer 2 with a thickness of about 15 μm is deposited, and the sample is taken out when the temperature in the chamber is lower than 100℃;

[0075] Third, the substrate 1 with the deposited piezoelectric layer 2 is placed in the plating machine, the target-to-substrate distance is 7 cm, the vacuum degree is 5 × 10 -3 Pa, and the plating temperature is 50℃;

[0076] Fourth, Ar and O2 are input, the gas pressure is 0.9 Pa, the Ar / O2 flow ratio is 1:1, the radio frequency power is 700 W, the plating time is 5.5 h, an AlCrNiSiTiTaYO high-entropy alloy oxide protective layer 3 with a thickness of about 4.0 μm is deposited, and the sample is taken out when the temperature in the chamber is lower than 50℃.

[0077] Fifth, an insulating ring is pasted on the substrate 1 with the deposited piezoelectric layer 2 and high-entropy alloy oxide protective layer 3. The purpose of the insulating ring is to form an inner and outer electrode area, which is convenient for ultrasonic signal testing. The insulating ring is made of polyester amide material, with a thickness of 0.15 mm, an inner diameter of 3 mm, and an outer diameter of 5 mm.

[0078] Sixth, the sample prepared in the fifth step is placed in the plating machine, the target-to-substrate distance is 12 cm, the vacuum degree is 5 × 10- 3 Pa, 50℃ of plating temperature;

[0079] Step 7, input Ar, 0.9 Pa of air pressure, 100 A of arc current, 1.5 min of plating time, and deposit a Cr bonding layer 4 with a thickness of about 500 nm.

[0080] Step 8, rotate the sample prepared in Step 7 to face the electrode target, 7 cm of target base distance, 5x10 -3 Pa, 50℃ of plating temperature;

[0081] Step 9, input Ar, 0.9 Pa of air pressure, 700 W of radio frequency power, 11 min of plating time, and deposit an Ag electrode layer 5 with a thickness of about 6.7 μm, and take out the sample when the temperature in the chamber is lower than 50℃.

[0082] Example 6

[0083] A preparation method of an ultrasonic sensor structure with enhanced high-temperature service performance, which is basically the same as that in Example 1, except that the AlCrNbSiTiO high-entropy alloy oxide protective layer 3 is prepared by a radio frequency magnetron sputtering method in Step 4.

[0084] Example 7

[0085] A preparation method of an ultrasonic sensor structure with enhanced high-temperature service performance, which is basically the same as that in Example 1, except that the AlCrNbSiTaTiO high-entropy alloy oxide protective layer 3 is prepared by a radio frequency magnetron sputtering method in Step 4.

[0086] Example 8

[0087] A preparation method of an ultrasonic sensor structure with enhanced high-temperature service performance, which is basically the same as that in Example 1, except that the AlCrNbSiTaTiVO high-entropy alloy oxide protective layer 3 is prepared by a radio frequency magnetron sputtering method in Step 4.

[0088] Example 9

[0089] A preparation method of an ultrasonic sensor structure with enhanced high-temperature service performance, which is basically the same as that in Example 1, except that the AlCrNbSiTaTiVZrO high-entropy alloy oxide protective layer 3 is prepared by a radio frequency magnetron sputtering method in Step 4.

[0090] Example 10

[0091] A preparation method of an ultrasonic sensor structure with enhanced high-temperature service performance, which is basically the same as that in Example 1, except that the AlCrSiTaTiZrO high-entropy alloy oxide protective layer 3 is prepared by a radio frequency magnetron sputtering method in Step 4.

[0092] Example 11

[0093] A method for preparing an ultrasonic sensor structure with enhanced high-temperature service performance, which is substantially the same as that of Example 1, except that in the fourth step, the AlCrNbSiTiVO high-entropy alloy oxide protective layer 3 is prepared by radio frequency magnetron sputtering.

[0094] Comparative Example 1

[0095] A method for preparing a temperature sensor structure, which comprises the following steps:

[0096] In the first step, a clean stainless steel substrate 1 is prepared and placed in a radio frequency magnetron sputtering coating machine, with a target-substrate distance of 5 cm and a vacuum degree of 5 x 10 -3 Pa, and a coating temperature of 200°C.

[0097] In the second step, Ar and O2 are input, with a gas pressure of 1.8 Pa, an Ar / O2 flow ratio of 2:1, a radio frequency power of 900 W, a bias voltage of 0 V, a coating time of 8 h, and a deposited thickness of the LiNbO3 piezoelectric layer 2 of about 16.7 μm.

[0098] In the third step, silver paste is applied to the surface of the piezoelectric layer 2, and after drying, a temperature sensor with a thickness of 200 μm is obtained.

[0099] Comparative Example 2

[0100] A method for preparing a temperature sensor structure, which is substantially the same as that of Example 1, except that there is no third step and no fourth step, i.e., there is no AlCrNiSiTiTaYO high-entropy alloy oxide protective layer 3, and a Cr bonding layer 4 and an AlCrNiSiTiTaY electrode layer 5 are directly deposited after the piezoelectric layer 2 is pasted with an insulating ring.

[0101] Comparative Example 3

[0102] A method for preparing a temperature sensor structure, which is substantially the same as that of Example 2, except that there is no AlCrNiSiTiTaYO high-entropy alloy oxide protective layer 3.

[0103] Comparative Example 4

[0104] A method for preparing a temperature sensor structure, which is substantially the same as that of Example 5, except that there is no AlCrNiSiTiTaYO high-entropy alloy oxide protective layer 3.

[0105] Comparative Example 5

[0106] A method for fabricating a temperature sensor structure is basically the same as in Example 1, except that: in the fourth step, the coating time is 16.5 h, and a high-entropy alloy oxide protective layer 3 of AlCrNiSiTiTaYO with a thickness of about 15 μm is deposited. Here, the sensor structure fails due to macroscopic cracks in the protective layer.

[0107] Comparative Example 6

[0108] A method for fabricating a temperature sensor structure is basically the same as in Example 1, except that the protective layer is usually SiO2.

[0109] The sensor structures prepared in the above embodiments and comparative examples were tested, and the test results are attached. Figures 1-9 As shown, the cross-sectional morphology, Cr element distribution, surface morphology of the AlCrNiSiTiTaY electrode layer, and surface morphology of the AlCrNiSiTiTaYO high-entropy alloy oxide protective layer of the sensor structure prepared in Example 1 are as follows: Figure 2 As shown, where, Figure 2 (a) shows the cross-sectional morphology of the sensor structure. It can be seen that the morphology of the LiNbO3 piezoelectric layer, the high-entropy alloy oxide protective layer and the high-entropy alloy electrode layer are relatively uniform. However, the Cr bonding layer is only 500 nm long and cannot be distinguished in the cross-sectional diagram of the sensor structure. Figure 2 (b) is a Cr element distribution map, which shows the presence of a clear Cr bonding layer; Figure 2 (c) shows the surface morphology of the AlCrNiSiTiTaY electrode layer; Figure 2 (d) shows the surface morphology of the AlCrNiSiTiTaYO high-entropy alloy oxide protective layer.

[0110] The ultrasonic signals of the sensor structures obtained in Examples 1, 2, and 1 (Comparative Example 1) were measured. The ultrasonic performance test parameters were: transmission voltage 100V and gain 60dB. The ultrasonic signal results for Examples 1 and 1 (Comparative Example 1) are as follows: Figure 3 As shown; the ultrasound signal results of Example 2 and Comparative Example 1 are as follows. Figure 4 As shown, the ultrasonic signals of the sensor structures in Examples 1, 2, and 1 (Comparative Example 1) are 5.2V, 3.16V, and 0.8V, respectively. These results demonstrate that the sensor structure designed in this invention, by adding an AlCrNiSiTiTaYO high-entropy alloy oxide protective layer and a Cr bonding layer, and using AlCrNiSiTiTaY high-entropy alloy electrodes and Ag electrodes, is more conducive to exciting strong ultrasonic signals compared to the traditional method of using silver paste to construct the electrodes of piezoelectric sensors. Furthermore, with other structures remaining the same, the AlCrNiSiTiTaY high-entropy alloy electrodes are more conducive to exciting strong ultrasonic signals than Ag electrodes.

[0111] The resistance of the sensor structure prepared by Example 1, Example 2, Comparative Example 2 and Comparative Example 3 was tested at a measurement frequency of 100 Hz. The resistance results of Example 1 and Comparative Example 2 are shown in Figure 5 The resistance results of Example 2 and Comparative Example 3 are shown in Figure 6 It can be seen that the resistance of Example 1, Example 2, Comparative Example 2 and Comparative Example 3 is 1.1 MΩ, 1.0 MΩ, 0.2 MΩ and 0.18 MΩ respectively, which shows that the high-entropy alloy oxide protective layer increases the resistance of the sensor structure, and higher resistance can prevent the piezoelectric layer from being broken down during high-voltage testing, thereby improving the working stability of the sensor structure in a high-voltage environment.

[0112] The resistance of the sensor structure prepared by Example 3 and Example 4 was also tested at a measurement frequency of 100 Hz, and the results are shown in Figure 7 It can be seen that the resistance of Example 3 and Example 4 is 1.6 MΩ and 2.3 MΩ respectively, which shows that the increase in the thickness of the high-entropy alloy oxide protective layer improves the resistance of the sensor structure and enhances the working stability of the sensor structure in a high-voltage environment.

[0113] The ultrasonic signal of the sensor structure was tested, and the ultrasonic signal of the sensor structure prepared by Example 1, Example 3, Example 4 and Comparative Example 5 was tested. The ultrasonic performance test parameters were: emission voltage 100 V, gain 60 dB, and the ultrasonic signal amplitude results are shown in Figure 8 It can be seen that the high-entropy alloy oxide protective layer of Comparative Example 5 is too thick, which not only wastes coating time, but also causes the coating to crack, so that the specific resistance of the sensor cannot be measured, and the sensor does not have ultrasonic excitation capability, that is, the thickness of the high-entropy alloy oxide protective layer should be less than 10 μm.

[0114] The high-temperature stability of the sensor structure was tested. After the ultrasonic signal of the sensor structure prepared by Example 5 and Comparative Example 4 was tested, the ultrasonic signal was tested after high-temperature annealing at 760℃, and the results are shown in Figure 9 Figure 9 (a) is a relative intensity diagram of the ultrasonic signal of the sensor structure of Example 5 and Comparative Example 4 after different annealing times; Figure 9 (b) is an ultrasonic signal diagram of the sensor structure of Example 5 after different annealing times; Figure 9 (c) is an ultrasonic signal diagram of the sensor structure of Comparative Example 4 after different annealing times. It can be seen that the ultrasonic signal intensity of the sensor structure prepared by Comparative Example 4 is only 10% of that before annealing after annealing at 760℃ for only 10 h; while the ultrasonic signal intensity of the sensor structure prepared by Example 5 can still maintain 20% of that before annealing after annealing at 760℃ for 100 h, which shows that the sensor structure prepared by the present application has stronger high-temperature resistance.​

[0115] In the test of the resistance and ultrasonic signal of the sensor structure constructed in test examples 6-11, similar performance to example 1 was found. It is illustrated that the high-entropy alloy oxide protective layer used in the present application significantly improves the sensor resistance, which not only prevents the piezoelectric layer from being broken down during high-voltage testing, improves the working stability of the sensor in a high-voltage environment, but also serves as a high-temperature protective layer, improving the high-temperature stability of the sensor.

[0116] The above has further described the present application with the help of specific examples, but it should be understood that the specific description here should not be understood as limiting the essence and scope of the present application, and various modifications made to the above examples by those skilled in the art after reading the specification are within the scope of the present application.

Claims

1. An ultrasonic sensor structure for enhanced high-temperature service performance, comprising, from bottom to top, a substrate, a piezoelectric layer, a protective layer, a bonding layer, and an electrode layer, characterized in that, The protective layer is a high-entropy alloy oxide with a thickness of 1~10μm, and the high-entropy alloy oxide is selected from at least one of AlCrNbSiTiO, AlCrNiSiTiTaYO, AlCrNbSiTaTiO, AlCrNbSiTaTiVO, AlCrNbSiTaTiVZrO, AlCrSiTaTiZrO, and AlCrNbSiTiVO.

2. The ultrasonic sensor structure according to claim 1, characterized in that, The piezoelectric layer is an oxide or nitride piezoelectric material with a thickness of 5~25μm.

3. The ultrasonic sensor structure according to claim 1, characterized in that, The bonding layer is at least one metallic material selected from Cr and Ti, and has a thickness of 100~600nm.

4. The ultrasonic sensor structure according to claim 1, characterized in that, The electrode layer is a solid metal element or a solid metal alloy with a thickness of 2~20μm, and the electrode layer is divided into an inner electrode region and an outer electrode region.

5. A method for fabricating an ultrasonic sensor structure as described in any one of claims 1 to 4, characterized in that, A piezoelectric layer, a protective layer, a bonding layer, and an electrode layer are sequentially prepared on the substrate surface; wherein the piezoelectric layer, the protective layer, and the electrode layer are prepared by radio frequency magnetron sputtering; and the bonding layer is prepared by arc ion plating.

6. The preparation method according to claim 5, characterized in that, During the radio frequency magnetron sputtering deposition, the target-substrate distance is 5~15cm, and the vacuum degree is 2×10⁻⁶. -3 ~6×10 -3 Pa, the coating temperature is 40~200℃; the arc current during the arc ion plating deposition is 80~110A, and the gas pressure is 0.8~1.5Pa.

7. The preparation method according to claim 5, characterized in that, The piezoelectric layer is an oxide. During preparation, Ar and O2 are input, the gas pressure is 0.8~2.1Pa, the Ar / O2 flow ratio is (1~6):1, the radio frequency power is 800~900W, the bias voltage is 0~30V, and the coating time is 4~10h.

8. The preparation method according to claim 5, characterized in that, The piezoelectric layer is a nitride. During preparation, Ar and N2 are input, the gas pressure is 0.8~2.1Pa, the Ar / N2 flow ratio is (1~3):1, the radio frequency power is 800~900W, and the coating time is 4~10h.

9. A temperature detection system, characterized in that, The ultrasonic sensor structure according to any one of claims 1 to 4 is provided, wherein the ultrasonic signal intensity remains at more than 20% of that before annealing after annealing at a high temperature of 760°C for 100 hours.

10. The temperature detection system according to claim 9, characterized in that, The sensor structure has a resistance of 1.0~2.3MΩ at a measurement frequency of 100Hz; The thickness of the high-entropy alloy oxide protective layer is 1~10μm, and the thickness is positively correlated with the resistance value; when the thickness is >10μm, the protective layer is prone to cracking, which can lead to sensor failure.